KUALITAS TERASI UDANG DENGAN SUPLEMENTASI PEDIOCOCCUS HALOPHILUS (FNCC-0033) - Nooryantini Sutikno; Yuspihana Fitrial; Rita Khairina (Fish Scientiae, 2019)
Terasi is condiment of formed solid, its flavour typically result of shrimp fermentation or mix of them with salt or other additional substance. The aim of this research is to know influence of the supplementation P. halophilus (FNCC-0033) isolate, to time of fermentation and quality of terasi shrimp. This research by complecated Randomized Design with 3 repetition’s. The treatment given are supplementation P. halophilus 2,5 x 104 CFU/g (A), P. halophilus 5,0 x 104 CFU/g (B) and processing terasi without addition P. halophilus (FNCC-0033) as control (treatmen O). Measure of chemical parameter total N, water content, TVB and pH, the microbiologis parameter are total microbe and total LAB, and parameter organoleptic are colour, odour and texture. The research conducting days fermentation by each every 7 days during 28 days fermentation. Based on TVB value total microbe and total lactid asid bacteria show that had been formed at 21th days fermentation. The result of analysis of varians showed differenct betwen observed day fermentation. The conclusion of this research showed processing terasi by supplementation of P. halophilus have similarity wich spontanious fermentations. The total microbe are supplementation to terasi able resulted of more fermentation time is quicker than spontanious fermentation.